STRUCTURAL FABRIC OF THE ANTOLA UNIT (RIVIERA DI LEVANTE, ITALY) AND IMPLICATIONS FOR ITS ALPINE VERSUS APENNINE ORIGIN - Corsi, Barbara; Elter, Franco Marco; Giammarino, Stani (Ofioliti, 2001)
A new tectonic interpretation of the Antola Unit is presented for the eastern Liguria (from Genova to Chiavari). Five tectonic episodes are recognizable, all developed in the brittle-ductile field. The first three tectonic episodes took place before the deposition of the Portofino Conglomerate (Early Oligocene) whereas the last two episodes are not quite defined. The first episode (F1) is characterized by rare folds with NW/SW vergence; the second episode (F2) is related to folds with SE vergence; the third episode (F3) is associated with sub vertical conjugate shear bands; the last two episodes are characterized by low angle shear planes (F4) with a top to NE/NW component of shear while the last episode (F5) is related to the transected cleavage folds with subvertical axial planes.The first three tectonic phases identified in the Antola Unit should be ascribed to the Alpine orogenesis; this interpretation agrees with that of Marroni and Pandolfi (1996) and of Ellero (1999; 2000) for the surrounding areas.